WIN EVERY DAY : proven practices for extraordinary results ; proven practices for extraordinary results. - Miller, Mark, 1959- (BERRETT-KOEHLER, 2020)
Great ideas don't matter if you can't execute--bestselling leadership expert Mark Miller offers a proven, research-based method for creating workplaces where everyone performs at the highest level. All high performance organizations have one thing in common: execution. The men and women who work there sustain performance at seemingly otherworldly levels of precision, accuracy, and consistency. In the fifth and final book of Mark Miller's High Performance series, he uses his trademark business fable format to show how any organization can cultivate the kind of everyday habits that yield extraordinary results. Miller tells the story of Blake Brown, a CEO who learns how to help his team to consistently excel at execution from a perhaps unlikely source: his son's high school football coach. The story is fictional, but the principles and practices are very real, derived from years of research led by a team from Stanford University. Miller and his team interviewed leaders and employees from numerous world-class organizations, including the Navy SEALS, Starbucks, Apple, Southwest Airlines, the Seattle Seahawks, Mayo Clinic, Cirque du Soleil, and more. The lessons learned were then field-tested with over seventy businesses employing over 7,000 people. Miller gives you proven tools to release the untapped potential in your people, create a strong competitive advantage, and win not just on game day but every day.